PEMBENTUKAN RASA BERUMAH DAN CULTURAL BELONGING TOKOH IMIGRAN PADA NOVEL TANAH SEBERANG (2018) - Farah Dibaj; Suma Riella Rusdiarti (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2022)
In literary works, how immigrants build a sense of home and culture can be seen in the novel titled Tanah Seberang (2018) by Kurnia Gusti Sawiji. This research using qualitative-descriptive method aims to show how the process of feeling at home and cultural belonging is built by immigrant characters in the novel Tanah Seberang (2018). This study will use the concept of narratology proposed by Gérard Genette (1983) and the theory of Home and Belonging and “in-between” Identity proposed by John McLeod (2000). The results showed (1) one novel contains variable focalization that represents the children's point of view, (2) in the process of the characters in building a sense of home and cultural belonging, there is contestation between Malaysia, other countries, and Indonesia, other countries. origin of the immigrants. The contestation of the country of origin, namely Indonesia, and the migrant country, namely Malaysia, shows that Malaysia can provide a good life from a financial perspective, however, the cultural belonging and sense of home of the migrant population in the novel are still embedded in their country of origin, Indonesia.